Deformation and Fracture of Ti-6Al-4V/TiC Composites 3D Printed using Wire-Feed Electron Beam Additive Manufacturing under Uniaxial Tensile Stress; Physical Mesomechanics; Vol. 28, iss. 6 - Panin A. V. Alexey Viktorovich; Kazachenok M. S. Marina Sergeevna; Shugurov A. R. Artur Rubinovich; Eremina G. M. Galina Maksimovna; Smolin A. Yu. Aleksey Yurjevich (2025, 2025)
Title screen